A Business Model to Support Sustainable Performance of Digital Startup Companies - Danarahmanto, Pri Agung; Azis, Yudi (CSID Journal of Infrastructure Development, 2019)
Digital startup companies have a high failure rate. The purpose of this research is to determine the effect of entrepreneurship orientation, innovation, customer participation, business model, and sustainable performance on startup companies. This research was conducted qualitatively using case study approach, and the data were collected using interview. The unit of analysis was a digital startup company in Indonesia with the observation unit being the founder or head of the company. The results showed that the business model was influenced by entrepreneurship orientation, innovation, and customer participation, while the sustainable performance was influenced by the business model. The implication of this research is the importance of developing business models and involving corporate leaders and customers in the company to support the sustainability of digital startup companies in Indonesia.